Distributed Economic Optimal Scheduling Scheme for Ship-Integrated Energy System Based on Load Prediction Algorithm - Zhang, Yuxin; Shan, Qihe; Teng, Fei; Li, Tieshan (Frontiers in Energy Research, 2021)
In order to enhance the safety navigation and promote the environmental protection, this paper takes the problem of energy management on ship integrated energy system into consideration. According to the characteristics of navigation, an intelligent ship energy management model, considering the social benefits and economic benefits simultaneously, has been proposed. Meanwhile, this paper analyzes a distributed optimal scheduling problem which considers renewable generation devices and energy storage system. Combined with electricity-power system and thermal-power system, we propose an optimal scheduling scheme to accurately meet the actual load demand based on the pre-results analyzed by the ensemble learning short-term load forecasting algorithm. In addition, the related stability analysis has been given. Further, a serious of simulation results have been presented, which denote that the proposed load forecasting algorithm can accurately analyze the short-term load demand trend, and the proposed optimization algorithm can effectively coordinate the economy and environmental protection.